IMPLEMENTASI SISTEM ABSENSI KARYAWAN MENGGUNAKAN BARCODE DAN GPS BERBASIS WEBSITE PADA PT INSCIENPRO INSTRUMENT INDONESIA - Tati Muniroh; Fitri Yanti (LPPM Politeknik Pratama Kendal, 2026)
This study aims to implement a web-based employee attendance system integrating barcode scanning and GPS as attendance verification mechanisms at PT Inscienpro Instrument Indonesia. The previous method relied on WhatsApp location sharing, which was manual and vulnerable to data manipulation. The system was developed using Extreme Programming (XP) methodology with PHP and MySQL. Testing used Black Box and White Box methods. Results show the system improves data accuracy, reduces fraud potential, and accelerates attendance recap processes.